Review of compounds and activities from mangrove Sonneratia genus and their endophytes - Bin Liu; Xin Wang; Yiming Wang; Xiaohong Chen; Xiaobao Jin; Xiongming Luo (KeAi Communications Co., Ltd., 2023)
Sonneratia is an important mangrove plant, and its fruit has been used as traditional medicine and food in southeast China. With recent research focusing on its compounds and activities, an increasing number of compounds with novel structures and excellent antitumor, antioxidant, and other activities have been discovered. This review covered the compounds and activities of six species of the genus Sonneratia and their endophytes. To date, 116 compounds of Sonneratia have been reported, including 26 terpenoids, 9 flavonoids, 17 phenols, 9 lignans, 27 acid lipids, 16 steroids, and 12 other compounds. The main activities of the compounds in Sonneratia are antioxidant, antitumor, liver protection, antibacterial, and antidiabetic. Research on the compounds of endophytes from Sonneratia was first reported in 2009, and 56 compounds have been isolated, which mainly include sesquiterpenes, peptides, phenanthropyran ring-structured acids, pyrones, and anthracene derivatives. Individual compounds have been produced in Sonneratia and their endophytes that have the same structural fragments, and their interactions with small molecules and sources require further study. Recent advances in the bioactivities and compounds in the Sonneratia genus and their endophytes were summarized in this review, which is useful for the future isolation and discovery of active compounds and research regarding chemical ecology from the perspective of secondary metabolites.